IMPLEMENTATION OF THE RSA CRYPTOGRAPHIC ALGORITHM IN THE QR-CODE ANDROID-BASED BUILDING PERMIT CHECKING APPLICATION - Darsanto Faiz; Rio Andriyat Krisdiawan; Dias Eka Prayuda (FKOM UNIKU, 2021)
The investment office and one-stop integrated service (DPMPTSP) of Kuningan regency issues various kinds of permits, one of which is a building permit (IMB) issued by the investment office and one-stop integrated service on the applicant's side. Research is motivated by the vulnerability of counterfeiting permits that have been granted by the investment service and one-stop integrated services. The purpose of this research is to create a system or information technology that can help to make it easier to check building permits, one of which is by using QR-Code technology. This system can scan code that has been encrypted with the RSA algorithm so that the code created is not easily faked or read with similar applications. RSA Cryptography Algorithm, an algorithm used to encrypt and decrypt data. The RSA algorithm itself is an asymmetric algorithm, so it has a public key and a private key. RSA has a basic encryption and decryption process in the concepts of prime numbers and modulo arithmetic. The decryption and encryption keys are both integers. The encryption key is not kept secret and is known to the public so that the encryption key is also known as the public key, but the key for decryption is secret.Keywords: DPMPTSP, QR-Code, RSA Cryptrographic Algorithm